The impact of ZIMSTAT data in financial planning in organisatons: a case study of ZIMSTAT - Chadenganga, Violet (Midlands State University, 2017)
The purpose of this study is to examine the impact of Zimbabwe National Statistical Agency data in financial planning in organisations. The study used quantitative methodology with self-administered questionnaires to obtain data from employees of the. Structured interviews were also used to determine the impact of ZIMSTAT data in financial planning of organisations. The results from the findings shows that there is statistical gap in developing countries. Limited literature using African data meant that the research could not be compared with previous researches. The results indicated that ZIMSTAT data have got a positive with the quality of financial planning of organisations. The findings of this research imply that ZIMSTAT needs to adopt another method in the production of official statistics so as to improve the quality of statistics.